(untitled) (Scottish Historical and Archaeological Internet Reports, 2008)
The immediate environs of the Grant’s complex are a rich palimpsest of archaeological remains, attested from a variety of sources, and the general area has considerable cropmark evidence of human activity from the later prehistoric onwards.